if p(x)=x*2-1 and q(x)=5(x-1),which expression is equivalent to (p-q)(x)?

Question

if p(x)=x*2-1 and q(x)=5(x-1),which expression is equivalent to (p-q)(x)?

in progress 0
Ben Gia 13 mins 2021-07-22T22:26:20+00:00 1 Answers 0 views 0

Answers ( )

    0
    2021-07-22T22:27:25+00:00

    Answer:

    (p - q)(x) = (x -1) (x - 4)

    Step-by-step explanation:

    Given

    p(x) = x^2 - 1

    q(x) = 5(x - 1)

    Required

    (p – q)(x)

    This is represented as:

    (p - q)(x) = p(x) - q(x)

    (p - q)(x) = x^2  - 1 - 5(x - 1)

    (p - q)(x) = x^2  - 1 - 5x + 5

    Collec like terms

    (p - q)(x) = x^2  - 5x + 5 - 1

    (p - q)(x) = x^2  - 5x + 4

    Expand

    (p - q)(x) = x^2 -4x - x + 4

    Factorize

    (p - q)(x) = x(x -4) - 1(x - 4)

    (p - q)(x) = (x -1) (x - 4)

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )